Physical Abuse Related Death of a Disabled Child in Nursery - Metin, Ali; Bilgin, Nursel Gamsız; Yıldırım, Veli (The Bulletin of Legal Medicine, 2014)
People with disabilities constitute a large portion of our society as approximately 12.3%. İndividuals with disabilities have been in the risk group of violence. Disabled people have been target of physical, sexual, economic, emotional violence such as children, women and elderly. As a result of the violence experience they may have physical, mental problems, increasing disabled level or die. Many national and international research include that people with disabilities are exposed to different type of violence especially physical and sexual violence. 9 year old child that had lived in disabled care service, exposed to severe violence and neglect from care service worker. To show the incidence and result of violence and neglect contribute destruction the source of violence. Key words: Disabled child, Physical abuse, Death.